PROTOTYPE POWER HOUSE SECURITY SYSTEM USING FACE IDENTIFICATION AND MICROCONTROLLER-BASED VEHICLE IDENTIFICATION - Aulia Firmanda, Lintang; Indrianto Sudjoko, Rifdian; Hariyadi, Setyo (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
The rapid development of technology has had an impact on the power house area which has become an important place in various places. In general, power houses are needed in office areas, shopping centers and airports. A place like a power house is a place with a lot of equipment, a lot of tools at quite expensive prices. But usually the security in the power house only uses a key or RFID to enter the area. This method is considered less effective because the level of security is low and prone to damage. In this study, the topic studied was a power house security system using face detection and vehicle detection. This study aims to maintain security at the airport power house. This tool is designed using Webcam to function as input to identify the user and vehicle number plate, then send the response to Arduino Uno as a microcontroller. There is an infrared sensor for detecting the entry and exit of vehicles. The name of the power house officer and the license plate of the vehicle will appear on the LCD screen display. The servo functions as an entry bar opener, the servo can be opened if the user can be recognized. The prototype functions well as a security system in an airport power house where the security of this system identifies the faces of power house officer with a high degree of accuracy. In addition, this prototype can also detect vehicle license plates. After testing, it means that to detect 1 face and 1 plate it takes approximately 5 seconds after which the bar will open. When exiting or closing the gate it only takes 1 second because when a vehicle passes the sensor, the barrier will automatically open.